Liver stiffness (Fibroscan®) is a predictor of all‐cause mortality in people with non‐alcoholic fatty liver disease. (27th September 2022) - Braude, Michael; Roberts, Stuart; Majeed, Ammar; Lubel, John; Prompen, Jirayut; Dev, Anouk; Sievert, William; Bloom, Stephen; Gow, Paul; Kemp, William
Abstract: Background and aims: Progressive liver fibrosis related to non‐alcoholic fatty liver disease (NAFLD) is associated with all‐cause and liver‐related mortality. We assessed vibration‐controlled transient elastography (VCTE) as a predictor of mortality. Method: Data from patients who underwent VCTE for NAFLD at four large health services in Victoria, Australia between the years 2008 and 2019 were linked to state‐wide data registries. Cause of death (COD) and predictors of all‐cause mortality were subsequently analysed using descriptive statistics and Cox‐proportional regression analysis. Results: Of 7079 VCTE records submitted for data linkage, 6341 were matched via data registry linkage. There were 217 deaths over a 22 653 person‐year follow‐up. COD included malignancies other than hepatocellular carcinoma (HCC) (18.0%, n  = 39), sepsis (16.1%, n  = 35), decompensated liver disease (15.2%, n  = 33), cardiac disease (15.2%, n  = 33) and HCC 6.0% ( n  = 13). Controlled attenuation parameter (CAP) was not associated with mortality in univariable analysis (HR = 1.00, CI 1.0–1.0, p  = .488). Increased liver stiffness measurement (LSM) (HR 1.02 per kiloPascal, CI 1.01–1.03, p < .001), Charlson comorbidity index (CCI) (HR 1.32 for each point, CI 1.27–1.38, p < .001) and age (HR 1.05 per annum, CI 1.03–1.07, p < .001) were each associated with higher rates of all‐cause mortality in multivariable analysis. LSM ≥10 kPa suggestive of compensated advanced chronic liver disease (cACLD) was associated with mortality in multivariable analysis (HR 2.31, CI 1.73–3.09, p  < .001). Conclusion: VCTE LSM, in addition to age and CCI, is independently associated with increased all‐cause mortality in a large cohort with NAFLD.